GAMBARAN TINGKAT PENGETAHUAN HIPERTENSI PADA LANSIA - Yestiani Norita Joni (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
High blood pressure or hypertension increases with age. The purpose of this study was to describe the level of knowledge of hypertension in the elderly. This study uses a descriptive method that will measure the knowledge of the elderly on hypertension. Based on the results of the study, it can be concluded that the level of knowledge of the elderly about hypertension in the low category is 48 people (69.6%) and the elderly prevention efforts regarding hypertension in the medium category are 38 people (55.1%).Keywords:Â Hypertension, Knowledge, Elderly